(untitled) (Sociologisk Forskning, 2000)
Sorokin on suicide This introduction to the following, previously unknown essay on suicide by Pitirim Sorokin analyzes the piece itself and its ideological background. It is noted that the later world-famous author was only one of the hundreds who wrote on the topic in Russia in the 1910s, at the time of the ”second suicide epidemic”. The piece itself was intended to convey the results of science to the masses and the publication was accordingly cheaply priced. From the outset, Sorokin presents largely Durkheimian ideas, but tends to draw his own conclusions from Durkheim ’s data. The main differences between the Master and the Disciple are Sorokin’s denial of the existence of the so-called ”altruistic suicide” in primitive society, his support of imitation as a factor in suicide, his thematic stress on ”the isolation of the individual” in modern society as the main cause of suicide and, especially, his statement that ”need, hunger, and unemployment” are in fact responsible for most suicides.